Articulação entre inovação, competências e desempenho organizacional: um estudo em organizações de Minas Gerais na área da Saúde - Leandro Pinheiro Cintra (2013)
The aim of this study was to analyze the linkage between innovation and competence management and their impact on the performance in public and private organizations of health sector of Minas Gerais. lt was necessary to determine the theoretical constructs of competence, innovation and organizational performance, to achieve the proposed objective in this study and also enable an appropriate methodological approach. This articulation is carried on this work for the health context in Brazil, which has a Health System (SUS) with peculiarities and complex environment for a human resource management at this area. The specitie objectives of the study included: analyze the competence management conduction in studied organizations; discuss how innovation processes take place in the organizations studied, considering the different perspectives, and investigate the consequences caused in driving innovation and competences, establishing relevant links and joints, mainly with organizational performance. The study on Secrctaria de Saúde do Estado de Minas Gerais (SESMG), Unimed Belo Horizonte and lnstituto de Previdência dos Servidores o Estado de Minas Gerais (IPSEMG) presents the project management as the primary management tool innovation used by healthcare institutions, coupled with systematic monitoring of institutional performance and strategic planning, with direct impact on organizational performance. The competence management is presented as a tool intended to improve the organizational performance, however, it was not observed as reality in the institutions studied because of the difficulties encountered in implementation.